1985
DOI: 10.1136/bjo.69.11.841
|View full text |Cite
|
Sign up to set email alerts
|

Role of the posterior capsule in the prevention of postoperative bacterial endophthalmitis: experimental primate studies and clinical implications.

Abstract: SUMMARYThe posterior capsule has an important effect on the risk of postoperative bacterial endophthalmitis. In order to investigate whether the posterior capsule inhibited the spread of infection into the vitreous we performed extracapsular cataract extraction in both eyes of 10 primates. In one eye of each primate the posterior capsule was left intact and in the other eye a large posterior capsulectomy was performed. When the anterior chambers were challenged with equivalent inocula of Staphylococcus aureus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 10 publications
4
22
3
Order By: Relevance
“…with or without implant), positive vitreous cultures are found in 80% of suspected cases. The fact that similar percentages of positive cultures are found (regardless of the technique used) would seem to indicate that the posterior capsule does not play any fundamental role in the limitation and spread of intraocular infections in humans, a finding which contrasts sharply with the results o f experimental studies [20].…”
Section: Lens Implantation Surgerycontrasting
confidence: 55%
“…with or without implant), positive vitreous cultures are found in 80% of suspected cases. The fact that similar percentages of positive cultures are found (regardless of the technique used) would seem to indicate that the posterior capsule does not play any fundamental role in the limitation and spread of intraocular infections in humans, a finding which contrasts sharply with the results o f experimental studies [20].…”
Section: Lens Implantation Surgerycontrasting
confidence: 55%
“…Clinically, we do not have the im pression that the posterior capsule is a possible barrier to the spread of postoperative infection from the anterior to the posterior chamber, first because the incidence of endophthalmitis is higher after extracapsular than after intracapsular surgery; second because in all our cases of endophthalmitis we have seen a vit reous involvement and finally because vitreous taps yield more often positive cultures than anterior chamber ones. This is of course in contrast with what has been found experimen tally [6,7].…”
Section: Intraocular Surgerycontrasting
confidence: 54%
“…Culture-positive endophthalmitis developed in the left eyes 72 h after injection, but failed to develop in the right eyes. These results were confirmed in a later study [93]in which the authors showed that the presence of a posterior chamber intraocular lens did not appreciably compromise the barrier function of the posterior capsule. In a similar study, Records and Iwen [94]used rabbits to determine if extracapsular lens extraction enhanced the ability of S. aureus to infect the anterior chamber and to assess the ability of the posterior capsule to act as a barrier against the spread of bacteria into the vitreous.…”
Section: General Information From Experimentalmodelssupporting
confidence: 79%